A programação no ensino médio como recurso de aprendizagem dos zeros da função polinomial do 2º grau - Siqueira, Fábio Rodrigues de (2012)
This research has as objective to check if the proposal of an algorithm to be converted into a computer program can contribute to the learning of an object of mathematical study. For that, we have formulated the following research question: how can the elaboration of a converted algorithm into a computer program help high school students in the learning of the zeros of the 2nd degree polynomial function? The research was conducted in two stages. The first stage, with two initial activities, consisted of two parts: the first one with a 1st year high school student in order to verify if the activities were appropriate to the research and in the second part, after the application of the two activities, we have selected four participants for the second stage that had presented different results. After the analysis of the first stage development, the activities were improved to the second one, composed of three activities, among which the software Visualg 2.0 was used for the algorithm edition and its conversion to a computer program. The APOS theory by Ed Dubinsky, theoretical support of the research, presents the action levels, process, object and scheme, that allow the verification of the individual`s capacity to develop actions over an object and think about its properties. The research participants had improvements in their learning, because besides developing a computer program to determine the zeros of 2nd degree polynomial function, they have started to elaborate other functions previewing their possible solutions, presenting all the levels of the APOS theory. As research methodology we have adopted the Design Experiments. We have justified its use, for adjustments could be done during the work development. Analyzing the activities which were done we have concluded that the students have achieved a satisfactory learning level over the object of study